Synthesis of chitosan nanoparticles (CSNP): effect of CH-CH-TPP ratio on size and stability of NPs - Des Bouillons-Gamboa, Rosvin E.; Montes de Oca, Gabriela; Baudrit, Jose Roberto Vega; Ríos Duarte, Liz Carolina; Lopretti, Mary; Rentería Urquiza, Maite; Zúñiga-Umaña, Juan Miguel; Barreiro, Filomena; Vázquez, Patricia (Frontiers in Chemistry, 2024)
In the face of a pressing global issue-the escalating threat of antibiotic resistance-the development of new antimicrobial agents is urgent. Nanotechnology, with its innovative approach, emerges as a promising solution to enhance the efficacy of these agents and combat the challenge of microbial resistance. Chitosan nanoparticles (CSNPs) stand out in biomedical applications, particularly in the controlled release of antibiotics, with their unique properties such as biocompatibility, stability, biodegradability, non-toxicity, and simple synthesis processes suitable for sensitive molecules. This study synthesized CSNPs using the ionotropic gelation method, with tripolyphosphate (TPP) as the crosslinking agent. Various CS: TPP ratios (6:1, 5:1, 4:1, 3:1, 2:1) were tested, and the resulting nanoparticles were evaluated using dynamic light scattering (DLS). The CS: TPP ratio of 4:1, with an average hydrodynamic diameter (DHP) of (195 ± 10) nm and a zeta potential of (51 ± 1) mV, was identified as the most suitable for further analysis. The characterization of NPs by Transmission Electron Microscope (TEM) and atomic force microscopy (AFM) revealed diameters of (65 ± 14) nm and (102 ± 18) nm, respectively. Notably, CSNPs exhibited significant aggregation during centrifugation and lyophilization, leading to diameter increases of up to 285% as measured by AFM. The antibacterial activity of CSNPs against Staphylococcus aureus and Escherichia coli was assessed using the resazurin assay. It was found that CSNPs not subjected to centrifugation, freezing, and lyophilization retained their antimicrobial activity. In contrast, those that underwent these processes lost their efficacy, likely due to aggregation and destabilization of the system. This study presents a straightforward and effective protocol for encapsulating sensitive active agents and synthesizing chitosan nanoparticles, a potential system with significant implications in the fight against antibiotic resistance.